7ROSES, a transdiagnostic intervention for promoting self-efficacy in traumatized refugees: a first quantitative evaluation. Issue 1 (31st December 2019) - van Heemstra, Henriette E.; Scholte, W. F.; Haagen, J. F. G.; Boelen, P. A.
ABSTRACT: Objective : Due to traumatic experiences and highly prevalent post-migration stressors, refugees are vulnerable for developing psychopathology. To date, research has mainly evaluated trauma-focused therapies, targeting post traumatic stresss symptoms. Treatments targeting post-migration stressors are relatively understudied. The present cohort study evaluated the potential effectiveness of 7ROSES, a transdiagnostic intervention that aims to increase self-efficacy among treatment-seeking refugees in dealing with post-migration stressors. Because it can be applied by non-specialist health care workers, it can be disseminated on a large scale, thereby increasing options for psychosocial support for refugees. Method : Forty-nine refugees (65% male, average age: 36.02 years, SD  = 8.52) with psychopathology were included. Before and after participation in 7ROSES, self-efficacy was measured using the General Self-Efficacy Scale (GSES), and general psychopathology using the Brief Symptom Inventory (BSI). Results : Completers analysis yielded a significant increase in GSES scores (Z = −2.16, p = .03) and significant decrease in BSI scores (Z = −2.05, p = .04) with medium-small effects (both r = −.28). Intent-to-treat analysis, using predictive mean matching imputation, yielded significant results for the GSES ( p = .012) but not for the BSI ( p = .14) with small effects (GSES r =  .14, BSI r = .12). Reliable change indices established negative change in 3%, no change in 70%, and positive change in 27% based on the GSES; percentages were 11.5%, 65.5%, and 23%, respectively, based on the BSI. Conclusion : Findings provide preliminary evidence that 7ROSES could improve self-efficacy and general mental health in refugees with psychopathology. HIGHLIGHTS: 7ROSES is a new low-intensity transdiagnostic treatment. 7ROSES aims to empower refugees with psychopathology in coping with post-migration problems. Around a quarter of 7ROSES participants reported an increased self-efficacy and mental health improvement.